Non-amino denitration dust removal catalytic filter bag as well as preparation method and application thereof

By using non-amino denitrification technology in SCR technology, using alcohols as reducing agents and CuO-MnO-NiO three-way catalysts, the problems of NH3 escape and ammonium bisulfate generation in the prior art were solved, and efficient and stable NOx removal and enhanced catalyst adhesion were achieved.

CN119548905AActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411779596.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing SCR technology has problems of NH3 escape and ammonium bisulfate generation during denitrification, which affects the system stability and atmospheric environment.

Method used

Non-amino denitrification technology is used to combine alcohols (such as methanol) as reducing agents, combining CuO-MnO-NiO three-way catalysts to achieve efficient removal of NOx, and enhance the adhesion between the catalyst and the filter bag matrix through additives such as SB powder.

Benefits of technology

The problems of NH3 escape and ammonium bisulfate generation were completely solved, the denitrification efficiency and catalyst stability were improved, and production costs were reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a non-amino denitration and dust removal catalytic filter bag as well as a preparation method and application thereof, and belongs to the technical field of waste incineration flue gas purification. The method comprises the following steps: dispersing an auxiliary agent into a solvent, adding nitric acid to obtain sol, adding catalyst powder into the sol, and uniformly dispersing to obtain matrix-loaded catalyst slurry; and spraying the obtained matrix loaded catalyst slurry on the pretreated filter bag matrix, drying and roasting to obtain the target product catalytic filter bag. The production efficiency of the catalytic filter bag is improved, and the production labor intensity of the catalytic filter bag is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste incineration flue gas purification, and specifically relates to a non-amino denitration and dust removal catalytic filter bag and a preparation method and application thereof. Background Art

[0002] Waste incineration technology has the advantages of volume reduction, quantity reduction, harmlessness, and resource utilization. However, pollutants such as HCl, SO2, NOx, particulate matter, heavy metals, and dioxins generated during the incineration process require a combination of multiple flue gas purification technologies for treatment, which results in complex systems and high costs. If the flue gas multi-pollutant synergistic removal technology is used to replace two or more removal technologies in the existing process, the process system can be effectively simplified, the floor space can be reduced, and the cost of pollutant removal can be reduced. The catalytic denitrification filter bag prepared by coupling the SCR denitrification catalyst with the dust removal filter material as the base load can achieve the synergistic and efficient removal of dust, NOx, and multiple pollutants.

[0003] The existing SCR technology for removing NOx from flue gas is that under the action of V2O5-WO3 / TiO2-based catalysts, at a certain temperature, NOx reacts with amino reducing agents such as ammonia or urea to generate harmless N2 and H2 O. However, there are two main problems with this technology. One is that NH3 reacts with SO2 in the flue gas to generate ammonium bisulfate, which blocks the pores of the catalyst and the flue gas pipes and valves, causing the catalyst to deactivate and affecting the stable operation of the system; the other problem is that in the actual operation process, excessive ammonia is sprayed to meet the denitrification effect, and NH3 escapes into the air, which will form ammonia salt particles with acidic substances in the air, affecting the atmospheric environment.

[0004] The SCR method using methanol instead of NH3 as a reducing agent can completely solve the problems of ammonium sulfate generation and ammonia escape. Patent CN 116265113 A discloses an integral extruded molecular sieve-based methanol-SCR denitration catalyst and its preparation method and application. The denitration catalyst uses a molecular sieve-based honeycomb ceramic as a matrix, including a nitrogen oxide reduction zone and a CO oxidation zone; the matrix in the CO oxidation zone is loaded with a transition metal composite oxide. CN 116920590 A discloses a denitration material and method for denitrifying cement kiln tail gas using methanol as a reducing agent, comprising independently packaged denitrifier A, denitrifier B and denitrifier C; lanthanum-cerium solid solution, waste vanadium-based denitrification catalyst and perovskite-type composite metal oxide are uniformly mixed and ground to form denitrifier A; coconut shell charcoal is crushed into small particles and uniformly mixed with carbide slag powder to form denitrifier B; OMS-2 is uniformly mixed with one or more of zirconium oxide, cobalt oxide and ferroferric oxide, and then electrolytic manganese slag is added and mixed uniformly and then ground to a certain particle size to form denitrifier C. The denitrifiers are added to the cement production process in different ways to synergistically exert denitrification effects and realize cement kiln denitrification.

[0005] The above-mentioned denitrification technology using methanol as a reducing agent requires a dedicated CO oxidation zone and the addition of multiple denitrification agents to achieve denitrification. The existing catalytic filter bags for coupling denitrification and dust removal also have problems such as low bonding strength between the catalyst and the filter material and relatively low denitrification efficiency. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, the present invention provides a non-amino denitration and dust removal catalytic filter bag and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a non-amino denitrification dust removal catalytic filter bag, the method comprising the following steps:

[0009] (1) Preparation of catalyst powder: adding an alcohol solvent to a dodecylamine solution and stirring to form a microemulsion; then adding copper salt, manganese salt and nickel salt to the emulsion, adding ammonia water after the salts are dissolved and adjusting to alkalinity, and finally performing a hydrothermal crystallization reaction. After the reaction is completed, centrifugation, washing, drying, roasting and grinding are performed in sequence to obtain catalyst powder;

[0010] (2) Preparation of substrate-supported catalyst slurry: dispersing the additive in a solvent and adding nitric acid to obtain a sol, adding catalyst powder to the sol and dispersing it uniformly to obtain a substrate-supported catalyst slurry;

[0011] (3) The substrate-loaded catalyst slurry obtained in step (2) is sprayed onto the pretreated filter bag substrate, dried and then calcined to obtain the target product catalytic filter bag.

[0012] In the above preparation method, the alcohol solvent in step (1) is n-butanol; the temperature of the hydrothermal crystallization reaction is 120-140° C., and the reaction time is 15-28 hours.

[0013] In the above preparation method, the drying temperature in step (1) is 110-150° C., and the drying time is 4-8 hours; the roasting temperature is 600-700° C., and the roasting time is 6-10 hours.

[0014] In the above preparation method, the mass ratio of CuO, MnO and NiO in the catalyst powder in step (1) is 1.0-3.0:1.0-2.0:0.5-1.5.

[0015] In the above preparation method, in step (2), the auxiliary agent is SB powder, carboxymethyl cellulose, or Tianqing powder; the mass concentration of the catalyst in the matrix-supported catalyst slurry is 1-10%. Preferably, the auxiliary agent is SB powder and carboxymethyl cellulose or Tianqing powder in a mass ratio of 1-20:0.1-1.

[0016] In the above preparation method, in step (3), the drying temperature is 105-115° C., the drying time is 3-6 h, and the roasting temperature is 160-220° C., the roasting time is 2-6 h.

[0017] A non-amino denitrification dust removal catalytic filter bag is prepared by the above method. Further, the catalytic filter bag has a loading capacity of 300 to 600 g / m 2 .

[0018] In the technical solution of the present invention, the catalyst filter bag prepared by the method is used as a catalyst for denitration and dust removal. Preferably, the catalytic reaction uses alcohol as a reducing agent, and more preferably, the reducing agent is methanol.

[0019] Further filter bag substrates include, but are not limited to, polyester materials such as polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), and polyimide (P84).

[0020] Furthermore, the application includes (1) catalytic partial pre-decomposition of methanol to form a methanol, H2, and CO steam mixture; (2) introducing the steam mixture into dust and NOx-containing waste incineration flue gas, the filter bag matrix removes the smoke, and the catalyst on the filter bag converts NOx into N2 and H2O, thereby achieving denitrification and dust removal of the catalytic filter bag.

[0021] The present invention provides a non-amino denitrification and dust removal catalytic filter bag prepared by the following method but not limited to the following method.

[0022] (1) Pre-treating the filter bag substrates of polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), and polyimide (P84) with 20% nitric acid to remove surface impurities at a temperature of 45°C for 2 hours, then washing with deionized water, and drying in a forced air drying oven at 105°C for 2 hours to obtain the pre-treated filter bag substrate;

[0023] (2) weighing an appropriate amount of dodecylamine and mixing with water, stirring, then adding an appropriate amount of n-butanol, stirring into a microemulsion; adding copper nitrate, manganese nitrate and nickel nitrate to the solution, after the salts are completely dissolved, adding ammonia water to the solution, adjusting the pH of the solution to 8-10, and then hydrothermally crystallizing the solution at 120-140° C. for 15-28 hours, then centrifuging the precipitated product, washing three times, drying at 110-150° C. for 4-8 hours, calcining at 600-700° C. for 6-10 hours, cooling naturally to room temperature, and grinding into a fine powder of 10-40 μm to obtain the non-amino denitration catalyst powder of the present invention;

[0024] (3) Add an appropriate amount of deionized water to a beaker, add SB powder, carboxymethyl cellulose / or Tianqing powder in sequence while stirring, then slowly add nitric acid with a concentration of 10% to obtain a uniform sol, then add the catalyst powder obtained in step (2), and ultrasonically homogenize for 2 to 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 1 to 10%;

[0025] (4) Use an automatic sprayer to apply the catalyst slurry on the filter bag substrate, dry it at 110°C for 3 to 6 hours, repeat the spraying 2 to 5 times, and calcine at 160 to 220°C for 2 to 6 hours to obtain a catalyst loading of 300 to 600 g / m 2 Catalytic filter material.

[0026] The beneficial effects of the invention are as follows: the invention provides a non-amino denitration dust removal catalytic filter bag and a preparation method and application thereof; a CuO-MnO-NiO ternary talc-like structure composition and a mixture thereof are non-amino denitration catalysts with high denitration efficiency; a non-amino methanol partial decomposition product (methanol, H2, CO steam mixture) is used as a denitration reducing agent, which completely eliminates the generation of ammonium sulfate (or ammonium bisulfate) and the problem of NH3 escape; at the same time, CO is used as a denitration reducing agent and is converted into CO2 during the denitration process without the need for special treatment; SB powder and an auxiliary agent are used to form a filter bag matrix loaded with a catalyst slurry, so that the matrix and the catalyst have stronger adhesion; automatic spraying technology is used to improve the production efficiency of the catalytic filter bag and reduce the labor intensity of the catalytic filter bag production.

[0027] Specific implementation scheme

[0028] The present invention will be further described below through specific examples, and all examples are operated completely according to the steps described in the present invention.

[0029] Example 1

[0030] (1) Treatment of filter bag substrate

[0031] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0032] (2) Preparation of Denitration Catalyst Composition Fine Powder

[0033] 1) Weigh 105.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to completely dissolve the dodecylamine in the n-butanol to obtain a microemulsion liquid; 3) Weigh 75.8g Cu(NO3)2.6H2O (98.0%), 100.0g Mn(NO3)2.4H2O (97.5%) and 39.7gNi(NO3)2.6H2O (98.0%) (weight ratio of CuO:MnO:NiO=1.0:1.0:0.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 8.5, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in an oven at 120°C, and the hydrothermal crystallization reaction is carried out for 24 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 120°C for 5 hours, calcined at 620°C for 8 hours, naturally cooled to room temperature, and ground into a fine powder of 10μm to obtain the non-amino denitration catalyst powder of the present invention.

[0034] (3) Preparation of substrate-supported catalyst slurry

[0035] 300 g of deionized water was added to a 1000 mL beaker, and 10.0 g of SB powder (68% on dry basis) and 0.2 g of carboxymethyl cellulose were added in sequence while stirring, and then 6.5 g of 10% nitric acid was slowly added dropwise to obtain a uniform sol, and then 12.5 g of the fine powder of the catalyst with a particle size of 10 μm obtained in step (2) was added, and ultrasonic homogenization was performed for 3 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 6.9%;

[0036] (4) Preparation of catalytic filter material

[0037] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 4 hours, sprayed three times, and calcined at 200°C for 4 hours to obtain a catalyst with a loading of 475 g / m 2 Catalytic filter material 1.

[0038] Example 2

[0039] (1) Treatment of filter bag substrate

[0040] The polyphenylene sulfide (PPS) filter bag material was placed in a beaker, and a 20% (mass concentration) nitric acid solution was added. The material was immersed in the beaker at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag matrix.

[0041] (2) Preparation of Denitration Catalyst Composition Fine Powder

[0042] 1) Weigh 105.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to completely dissolve the dodecylamine in the n-butanol to obtain a microemulsion liquid; 3) Weigh 84.2g Cu(NO3)2.6H2O (98.0%), 83.3g Mn(NO3)2.4H2O (97.5%) and 44.1gNi(NO3)2.6H2O (98.0%) (weight ratio of CuO:MnO:NiO=2.0:1.5:1.0) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 8.5, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in an oven at 130°C, and the hydrothermal crystallization reaction is carried out for 26 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 120°C for 5h, calcined at 660°C for 8 hours, naturally cooled to room temperature, and ground into a fine powder of 10μm to obtain the non-amino denitration catalyst powder of the present invention.

[0043] (3) Preparation of substrate-supported catalyst slurry

[0044] 300 g of deionized water was added to a 1000 mL beaker, and 12.5 g of SB powder (68% on dry basis) and 0.3 g of carboxymethyl cellulose were added in sequence while stirring, and then 9.8 g of nitric acid with a concentration of 10% was slowly added dropwise to obtain a uniform sol, and then 17.5 g of fine powder of the catalyst with a particle size of 15 μm obtained in step (2) was added, and ultrasonic homogenization was performed for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 7.6%;

[0045] (4) Preparation of catalytic filter material

[0046] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 3 hours, sprayed 4 times, and calcined at 180°C for 5 hours to obtain a catalyst loading of 382 g / m 2 Catalytic filter material 2.

[0047] Example 3

[0048] (1) Treatment of filter bag substrate

[0049] Place the polyimide (P84) filter bag material in a beaker, add a 20% (mass concentration) nitric acid solution, immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0050] (2) Preparation of Denitration Catalyst Composition Fine Powder

[0051] 1) Weigh 105.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to completely dissolve the dodecylamine in the n-butanol to obtain a microemulsion liquid; 3) Weigh 94.7g Cu(NO3)2.6H2O (98.0%), 20.0g Mn(NO3)2.4H2O (97.5%) and 59.5gNi(NO3)2.6H2O (98.0%) (weight ratio of CuO:MnO:NiO=2.5:1.0:1.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.5, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in an oven at 125°C, and the hydrothermal crystallization reaction is carried out for 28 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 140°C for 5h, calcined at 700°C for 6 hours, naturally cooled to room temperature, and ground into a fine powder of 25μm to obtain the non-amino denitration catalyst powder of the present invention.

[0052] (3) Preparation of substrate-supported catalyst slurry

[0053] Add 300 g of deionized water into a 1000 mL beaker, add 5.5 g of SB powder (68% on dry basis) and 0.3 g of carboxymethyl cellulose in sequence while stirring, then slowly drop 4.8 g of 10% nitric acid to obtain a uniform sol, then add 5.5 g of the fine powder of the catalyst with a particle size of 15 μm obtained in step (2), and homogenize by ultrasonication for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 3.6%;

[0054] (4) Preparation of catalytic filter material

[0055] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 6 hours, sprayed repeatedly for 5 times, and calcined at 170°C for 6 hours to obtain a catalyst loading of 512 g / m 2 Catalytic filter material 3.

[0056] Example 4

[0057] (1) Treatment of filter bag substrate

[0058] Place the polytetrafluoroethylene (PTFE) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a blast drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0059] (2) Preparation of Denitration Catalyst Composition Fine Powder

[0060] 1) Weigh 105.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to make the dodecylamine completely dissolved in n-butanol to obtain a microemulsion liquid; 3) Weigh 87.5g Cu(NO3)2.6H2O (98.0%), 75.0g Mn(NO3)2.4H2O (97.5%) and 45.6gNi(NO3)2.6H2O (98.0%) (weight ratio of CuO:MnO:NiO=3.0:2.0:1.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.0, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in a 140°C oven, and the hydrothermal crystallization reaction is carried out for 18 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 150°C for 4 hours, roasted at 680°C for 6 hours, and naturally cooled to room temperature, and then ground into a fine powder of 25μm to obtain the non-amino denitration catalyst powder of the present invention.

[0061] (3) Preparation of substrate-supported catalyst slurry

[0062] Add 300 g of deionized water into a 1000 mL beaker, add 3.5 g of SB powder (68% on dry basis) and 0.2 g of carboxymethyl cellulose in sequence while stirring, then slowly dropwise add 3.8 g of 10% nitric acid to obtain a uniform sol, then add 2.5 g of the fine powder of the catalyst with a particle size of 35 μm obtained in step (2), and homogenize by ultrasonication for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 2.0%;

[0063] (4) Preparation of catalytic filter material

[0064] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed three times, and calcined at 220°C for 3 hours to obtain a catalyst loading of 585 g / m 2 Catalytic filter material 4.

[0065] Example 5

[0066] (1) Treatment of filter bag substrate

[0067] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0068] (2) Preparation of Denitration Catalyst Composition Fine Powder

[0069] 1) Weigh 105.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to completely dissolve the dodecylamine in the n-butanol to obtain a microemulsion liquid; 3) Weigh 70.8g Cu(NO3)2.6H2O (98.0%), 125.0g Mn(NO3)2.4H2O (97.5%) and 24.8gNi(NO3)2.6H2O (98.0%) (weight ratio of CuO:MnO:NiO=1.5:2.0:0.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.0, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in a 120°C oven, and the hydrothermal crystallization reaction is carried out for 24 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 130°C for 4 hours, calcined at 650°C for 8 hours, naturally cooled to room temperature, and ground into a fine powder of 40μm to obtain the non-amino denitration catalyst powder of the present invention.

[0070] (3) Preparation of substrate-supported catalyst slurry

[0071] 300 g of deionized water was added to a 1000 mL beaker, and 15.5 g of SB powder (68% on dry basis) and 0.3 g of carboxymethyl cellulose were added in sequence while stirring, and then 20.5 g of nitric acid with a concentration of 10% was slowly added dropwise to obtain a uniform sol, and then 20.0 g of the fine powder of the catalyst with a particle size of 40 μm obtained in step (2) was added, and ultrasonic homogenization was performed for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 10.0%;

[0072] (4) Preparation of catalytic filter material

[0073] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 6 hours, sprayed twice, and calcined at 200°C for 6 hours to obtain a catalyst with a loading of 535 g / m 2 Catalytic filter material 5.

[0074] Example 6

[0075] (1) Treatment of filter bag substrate

[0076] The polyphenylene sulfide (PPS) filter bag material was placed in a beaker, and a 20% (mass concentration) nitric acid solution was added. The material was immersed in the beaker at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag matrix.

[0077] (2) Preparation of Denitration Catalyst Composition Fine Powder

[0078] 1) Weigh 105.5g dodecylamine, dissolve it in 1500mL deionized water, add it to a three-necked flask, and start stirring; 2) Weigh 1000mL n-butanol (mass percentage concentration ≥ 99.5), add it to the above three-necked flask, and stir to completely dissolve the dodecylamine in the n-butanol to obtain a microemulsion liquid; 3) Weigh 63.1g Cu(NO3)2.6H2O (98.0%), 83.3g Mn(NO3)2.4H2O (97.5%) and 66.1gNi(NO3)2.6H2O (98.0%) (weight ratio of CuO:MnO:NiO=1.5:1.5:1.5) are added into a three-necked flask; 4) when the solid is completely dissolved, an appropriate amount of ammonia water is added to adjust the pH value to 9.0, and the liquid is placed in a 5000ml reactor; 5) the reactor is placed in a 120°C oven, and the hydrothermal crystallization reaction is carried out for 26 hours. The product is centrifuged, washed twice with water, washed twice with alcohol, dried at 125°C for 6 hours, calcined at 680°C for 8 hours, and naturally cooled to room temperature, and then ground into a fine powder of 15μm to obtain the non-amino denitration catalyst powder of the present invention.

[0079] (3) Preparation of substrate-supported catalyst slurry

[0080] Add 300 g of deionized water into a 1000 mL beaker, add 10.5 g of SB powder (68% on dry basis) and 0.3 g of Tianqing powder in sequence while stirring, then slowly drop 15.5 g of nitric acid with a concentration of 10% to obtain a uniform sol, then add 12.0 g of fine powder of the catalyst with a particle size of 15 μm obtained in step (2), and ultrasonically homogenize for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 6.7%;

[0081] (4) Preparation of catalytic filter material

[0082] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed 4 times, and calcined at 180°C for 2 hours to obtain a catalyst loading of 435 g / m 2 Catalytic filter material 6.

[0083] Example 7

[0084] (1) A polytetrafluoroethylene (PTFE) filter bag substrate is obtained by using the filter bag substrate treatment method of step (1) of implementation 1.

[0085] (2) Add 300 g of deionized water to a 1000 mL beaker, add 10.5 g of SB powder (68% on dry basis) and 0.3 g of Tianqing powder in sequence while stirring, then slowly add 15.5 g of nitric acid with a concentration of 10% to obtain a uniform sol, then add 6.0 g of the fine powder of the catalyst obtained in step (2) of Example 1 and 4.0 g of the fine powder of the catalyst obtained in step (2) of Example 4, respectively, and ultrasonically homogenize for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 6.2%;

[0086] (4) Preparation of catalytic filter material

[0087] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 3 hours, sprayed three times, and calcined at 210°C for 5 hours to obtain a catalyst with a loading of 475 g / m 2 Catalytic filter material 7.

[0088] Example 8

[0089] (1) A polyphenylene sulfide (PPS) filter bag substrate is obtained by implementing the filter bag substrate treatment method of step (1) in step 2.

[0090] (2) 300 g of deionized water was added to a 1000 mL beaker, and 10.5 g of SB powder (68% on dry basis) and 0.3 g of carboxymethyl cellulose were added in sequence while stirring, and then 15.5 g of 10% nitric acid was slowly added dropwise to obtain a uniform sol, and then 5.0 g of the fine powder of the catalyst obtained in step (2) of Example 2 and 5.0 g of the fine powder of the catalyst obtained in step (2) of Example 5 were added respectively, and ultrasonic homogenization was performed for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 6.2%;

[0091] (4) Preparation of catalytic filter material

[0092] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed 4 times, and calcined at 200°C for 6 hours to obtain a catalyst loading of 515 g / m 2 Catalytic filter material 8.

[0093] Comparative Example 1

[0094] (1) Treatment of the filter bag substrate and (2) Preparation of the denitration catalyst composition fine powder are exactly the same as the first two steps of Example 3

[0095] (3) Add 300 g of deionized water and 3.7 g of carboxymethyl cellulose in a 1000 mL beaker while stirring, then slowly dropwise add 3.8 g of 10% nitric acid to obtain a uniform sol, then add 2.5 g of the fine powder of the catalyst with a particle size of 35 μm obtained in step (2), and ultrasonically homogenize for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 2.0%;

[0096] (4) Preparation of catalytic filter material

[0097] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 4 hours, sprayed three times, and calcined at 160°C for 6 hours to obtain a catalyst with a loading of 285 g / m 2 Comparative catalytic filter material 1.

[0098] Comparative Example 2

[0099] (1) Treatment of the filter bag substrate and (2) Preparation of the denitration catalyst composition fine powder are exactly the same as the first two steps of Example 6

[0100] (3) Add 300 g of deionized water to a 1000 mL beaker, add 10.8 g of Tianqing powder while stirring, then slowly drop 15.5 g of 10% nitric acid to obtain a uniform sol, then add 12.0 g of the fine powder of the catalyst with a particle size of 15 μm obtained in step (2), and ultrasonically homogenize for 4 hours to obtain a matrix-supported catalyst slurry with a mass concentration of 6.7%;

[0101] (4) Preparation of catalytic filter material

[0102] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 6 hours, sprayed 4 times, and calcined at 185°C for 4 hours to obtain a catalyst loading of 205 g / m 2 Comparative catalytic filter material 2.

[0103] Performance Testing

[0104] The performance evaluation of a non-amino denitrification dust removal catalytic filter bag prepared in the above examples and comparative examples was carried out by putting the catalytic filter bag on the sleeve. The evaluation conditions were: the NO concentration in the flue gas was 420 mg / m 3 , O2 volume fraction is 10%, water vapor content is 15% (volume ratio), SO2 concentration is 400mg / m 3 , dust concentration 2000mg / m 3, methanol is carried by water vapor into the methanol pre-decomposition bed, the methanol / NO range is 1.05-1.40, the carrier gas is N2, the evaluation temperature range is 160-240℃, the evaluation temperature is 210℃, the methanol / NO is 1.10, and the filtration wind speed is 0.75m / min (filter bag size). The performance of the catalytic filter bag is evaluated by the changes in the inlet and outlet NO and dust concentrations. The results are shown in Table 1.

[0105] Table 1 Evaluation of denitrification and dust removal performance of catalytic filter bags

[0106] Group Denitrification rate, % Dust removal efficiency, % Example 1 98.1 99.1 Example 2 98.7 98.9 Example 3 98.2 97.9 Example 4 99.1 98.4 Example 5 98.4 98.7 Example 6 96.5 98.6 Example 7 97.4 99.2 Example 8 98.1 98.5 Comparative Example 1 75.2 97.6 Comparative Example 2 68.4 98.7

[0107] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by this embodiment, that is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.

Claims

1. A method for preparing a non-amino denitrification dust removal catalytic filter bag, characterized in that: The method comprises the following steps: (1) Preparation of catalyst powder: adding an alcohol solvent to a dodecylamine solution and stirring to form a microemulsion; then adding copper salt, manganese salt and nickel salt to the emulsion, adding ammonia water after the salts are dissolved and adjusting to alkalinity, and finally performing a hydrothermal crystallization reaction. After the reaction is completed, centrifugation, washing, drying, roasting and grinding are performed in sequence to obtain catalyst powder; (2) Preparation of substrate-supported catalyst slurry: dispersing the additive in a solvent and adding nitric acid to obtain a sol, adding catalyst powder to the sol and dispersing it uniformly to obtain a substrate-supported catalyst slurry; (3) The substrate-loaded catalyst slurry obtained in step (2) is sprayed onto the pretreated filter bag substrate, dried and then calcined to obtain the target product catalytic filter bag.

2. The method for preparing a non-amino denitration and dust removal catalytic filter bag according to claim 1, characterized in that: In step (1), the alcohol solvent is n-butanol; the temperature of the hydrothermal crystallization reaction is 120-140° C., and the reaction time is 15-28 h; The mass ratio of dodecylamine, deionized water and n-butanol in the microemulsion liquid is 0.5-2:10-20:5-15; The mass ratio of the metal salt to the microemulsion liquid is 15-25:20-30.

3. The method for preparing a non-amino denitration dust removal catalytic filter bag according to claim 1, characterized in that: In step (1), the drying temperature is 110-150° C., and the drying time is 4-8 hours; the roasting temperature is 600-700° C., and the roasting time is 6-10 hours.

4. The method for preparing a non-amino denitration and dust removal catalytic filter bag according to claim 1, characterized in that: In step (1), the weight ratio of CuO, MnO and NiO in the catalyst powder is 1.0-5.0:1.0-5.0:0.5-3; Preferably, the weight ratio of CuO, MnO and NiO in the catalyst powder in step (1) is 1.0-3.0:1.0-2.0:0.5-1.

5.

5. The method for preparing a non-amino denitration dust removal catalytic filter bag according to claim 1, characterized in that: In step (2), the mass concentration of the catalyst in the matrix-supported catalyst slurry is 1 to 10% by weight of two of the auxiliary agents SB powder, carboxymethyl cellulose and Tianqing powder; Preferably, the auxiliary agent is a combination of SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder in a mass ratio of 1-20:0.1-1.

6. The method for preparing a non-amino denitration and dust removal catalytic filter bag according to claim 1, characterized in that: In step (3), the drying temperature is 105-115° C., the drying time is 3-6 hours, the roasting temperature is 160-220° C., and the roasting time is 2-6 hours.

7. A non-amino denitrification dust removal catalytic filter bag, characterized in that: The invention is prepared by the method according to any one of claims 1 to 6.

8. The non-amino denitrification dust removal catalytic filter bag according to claim 7, characterized in that: Catalytic filter bag loading 300~600g / m 2 .

9. Application of the catalyst filter bag prepared by the method of claim 1 as a catalyst in denitration and dust removal. Preferably, the catalytic reaction uses alcohol as a reducing agent, and more preferably, the reducing agent is methanol.

Citation Information

Patent Citations

  • Integral extrusion type molecular sieve based methanol-SCR denitration catalyst and preparation method and application thereof

    CN116265113A

  • Denitration material and method for denitration of cement kiln tail gas by using methanol as reducing agent

    CN116920590A

  • Methanol aromatization technology

    CN104098418A

  • Iron oxide carbon nitride heterojunction photocatalyst and preparation method thereof

    CN110252377A

  • Nickel-iron hydrotalcite and preparation method and application thereof

    CN110282666A